OPPORTUNITIES FOR IMPROVING THE FINANCIAL INDICATORS DESCRIBING THE COMPETITIVENESS OF COMMERCIAL BANKS (Marketing Journal, 2025)
This article thoroughly examines the concept of commercial banksʼ competitiveness and analyzes the opinions of domestic and foreign scholars on this matter. The main factor in ensuring the competitiveness of banks is the stability of the bankʼs liabilities and the regulatory level of demand deposits. Within the framework of the study, the analytical data of transnational banks of developed countries - Bank of America, Paribasbank, and major joint -stock commercial banks of the Republic of Uzbekistan - Uzmill iybank, Asaka Bank, and Sanoatqurilish bank were studied, and an analysis of the level of stability and competitiveness of their liabilities was conducted. 527
Keywords: bank; competitiveness; passive; credit; interest; deposit; securities; return on capital; gross deposits; demand deposits; interbank loans; inflation